Pengaruh Perencanaan Pajak, Kebijakan Dividen, dan Tingkat Inflasi Terhadap Nilai Perusahaan - Evi Septiyani; Yenni Cahyani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of tax planning, dividend policy, and inflation on firm value in real estate and property companies listed on the Indonesia Stock Exchange during the 2019–2024 period. The research was conducted using a quantitative approach with panel data analysis. The population of this study consists of all real estate and property companies listed on the Indonesia Stock Exchange, while the sample was selected using purposive sampling techniques based on predetermined criteria. A total of 11 companies were selected as the research sample. The data analysis method used in this study was panel data regression analysis processed with EViews 12 software. The results indicate that tax planning, dividend policy, and inflation simultaneously have a significant effect on firm value. Partially, tax planning has a significant effect on firm value, indicating that effective tax management can increase investor confidence and company performance. Dividend policy also has a significant effect on firm value, reflecting the importance of dividend distribution in attracting investors and increasing market valuation. Meanwhile, inflation does not have a significant effect on firm value, indicating that changes in inflation rates do not directly influence the value of companies in the real estate and property sector.